Exploration of Digital Transformation Through Agricultural Product Marketing Business Management Information System in Farmer Groups in Labuhan Bilik - Muttaqin, Alfin; Chetrine, Ema; Kurniasih, Kurniasih; Endah, Lely; Sudarmaji, Sudarmaji; Sumitro, Sumitro (Lembaga Riset Mutiara Akbar, 2025)
This study aims to explore how farmer groups in Labuhan Bilik adopt and implement the Business Management Information System (BIIS) in marketing agricultural products, as well as its impact on market access, transaction transparency, and farmer income. The method used is a qualitative case study approach through in-depth interviews, observations, and documentation of digital marketing activities. The results of the study indicate that the implementation of BIIS through social media, local e-commerce applications, and digital recording of harvest results has expanded market reach, accelerated distribution, and increased price transparency. However, the obstacles that arise include low digital literacy of farmers, limited technological infrastructure, and dependence on individuals who master technology. Therefore, ongoing assistance, digital literacy training, and collaboration between various parties are needed to ensure the sustainability of digital transformation. These findings are expected to be a strategic reference for policy makers and practitioners in formulating inclusive and adaptive agricultural digitalization programs.